Books & Bones & Other Things - Coetzee, Jan K (UJ Press, 2018)
Books tell stories about our lifeworld. In this book Jan Coetzee invites us to critically inquire into the aims, the content, and the context of the stories contained in a collection of old books from an old world. Without opening these old texts and without converting the original print on the pages to meaning and message, Coetzee brings the books into a dialogue with each other. Together with accompanying sculpted and/or found objects these books take on a new, broader function. By gathering them in one volume they attain a different character and tell us more than what the individual books ever could.